Truthfulness and Relevance in Telling The Time - Van der Henst, Jean-Baptiste; Kloetzer, Laure; Sperber, Dan (My University, 2002)
Someone asked ‘What time is it?’ when her watch reads 3:08 is likely to answer ‘It is 3:10.’ We argue that a fundamental factor that explains such rounding is a psychological disposition to give an answer that, while not necessarily strictly truthful or accurate, is an optimally relevant one (in the sense of relevance theory) i.e. an answer from which hearers can derive the consequences they care about with minimal effort. A rounded answer is easier to process and may carry the same consequences as one that is accurate to the minute. Hence rounding is often a way of optimising relevance. Three simple experiments give support and greater precision to the view that relevance is more important than strict truthfulness in verbal communication.